Research Methods for Business Students / Second Edition - Lewis Philip; Saunders Mark; Thornhill Adrian (Financial Times - Prentice Hall)
This text provides students with the necessary knowledge and skills for the successful completion of a piece of business research. The Nature of Business and Management Research and How to Use This Book, Formulating and Clarifying the Research Topic, Critically Reviewing the Literature, Deciding on the Research Approach and Choosing a Research Strategy, Negotiating Access and Research Ethics, Selecting Samples, Using Secondary Data, Collecting Primary Data Through Observation, Collecting Primary Data Using Semi-Structured and In-Depth Interviews, Collecting Primary Data Using Questionnaires, Analysing Quantitative Data, Analysing Qualitative Data, Writing Your Project Report, Bibliography, Appendices, Index.